Profil Kompetensi Profesional Mahasiswa Calon Guru - Sukri, Akhmad; Mursali, Saidil; Suyasih, Made; Sudana, I Ketut; Purnawati, Ni Komang; Laksmi, Ni Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The purpose of this study was to describe the professional competence of prospective teacher students. This research is a descriptive study with the subject of 30 students who take PPL/PLP activities in eight high school and MA schools in Central Lombok Regency, West Nusa Tenggara Province. Data collection was carried out through real teaching using an assessment score of 1 - 4 with details, 1 = not good, 2 = quite good, 3 = good, and 4 = very good. Students' professional competency scores were then averaged, then grouped into 4 categories, namely 3 < Score 4 (Very Good), 2 < Score 3 (Good), 1 < Score 2 (Good Enough), Score = 1 (Poor Well). The results showed that the students' professional competence was in the very good category, with a mean score of 3.25. These results indicate the need to improve the quality of learning and training for student teacher candidates, so that their professional competence can be maintained and improved.